“Implementación de una secadora giratoria de cacao automatizada a base de aire caliente con capacidad de 150 kilogramos” - Chimborazo Aguaisa, German Fabricio (2021)
This project arises from a need in the Calabi de Sillagua site, belonging to the Canton of Pangua, since there are a large number of cocoa crops where in winter times an important economic value is lost as the product cannot be dried. This motivated to implement an automatic cocoa drying machine that meets the characteristics of efficient drying and reduces drying time. This project is carried out in the SolidWorks program for the mechanical design of the elements, where the exact measurements for the construction of the machine are projected. In addition, it has an automatic control panel with elements such as pushbuttons, contactors and control and maneuvering equipment. The control panel allows to monitor the drying variables and the energization of the power equipment of the machine to achieve the product with the desired humidity characteristics. This machine is made with a capacity of 150 kilograms, it incorporates an air suction device with centrifugal turbines, a burner based on liquefied petroleum gas, the most important part of the project is automation, which allows automatic control of the speed of a motor - reducer coupled to the paddle remover, to improve drying times.